Osteology of the axial skeleton of Aucasaurus garridoi: phylogenetic and paleobiological inferences - Baiano, Mattia Antonio (2023)
Aucasaurus garridoi is an abelisaurid theropod from the Anacleto Formation (lower Campanian, Upper Cretaceous) of Patagonia, Argentina. The holotype of Aucasaurus garridoi includes cranial material, axial elements, and almost complete fore- and hind limbs. Here we present a detailed description of the axial skeleton of this taxon, along with some paleobiological and phylogenetic inferences. The presacral elements are somewhat fragmentary, although these show features shared with other abelisaurids. The caudal series, to date the most complete among brachyrostran abelisaurids, shows several autapomorphic features including the presence of pneumatic recesses on the dorsal surface of the anterior caudal neural arches, a tubercle lateral to the prezygapophysis of mid caudal vertebrae, a marked protuberance on the lateral rim of the transverse process of the caudal vertebrae, and the presence of a small ligamentous scar near the anterior edge of the dorsal surface in the anteriormost caudal transverse process. The detailed study of the axial skeleton of Aucasaurus garridoi has also allowed us to identify characters that could be useful for future studies attempting to resolve the internal phylogenetic relationships of Abelisauridae. Computed tomography scans of some caudal vertebrae show pneumatic traits in neural arches and centra, and thus the first reported case for an abelisaurid taxon. Moreover, some osteological correlates of soft tissues present in Aucasaurus and other abelisaurids, especially derived brachyrostrans, underscore a previously proposed increase in axial rigidity within Abelisauridae.